CCR5/CXCR3 antagonist TAK-779 prevents diffuse alveolar damage of the lung in the murine model of the acute respiratory distress syndrome - Chernov, Aleksandr S.; Rodionov, Maksim V.; Kazakov, Vitaly A.; Ivanova, Karina A.; Meshcheryakov, Fedor A.; Kudriaeva, Anna A.; Gabibov, Alexander G.; Telegin, Georgii B.; Belogurov, Alexey A. (Frontiers in Pharmacology, 2024)
The acute respiratory distress syndrome (ARDS) secondary to viral pneumonitis is one of the main causes of high mortality in patients with COVID-19 (novel coronavirus disease 2019) – ongoing SARS-CoV-2 infection, reached more than 0.7 billion registered cases. Recently we elaborated non-surgical and reproducible method of unilateral total diffuse alveolar damage (DAD) of the left lung in ICR mice – a publicly available imitation of the ARDS caused by SARS-CoV-2. Our data reads that two C-C chemokine receptor 5 (CCR5) ligands – macrophage inflammatory proteins (MIP) – (MIP-1/CCL3) and (MIP-1/CCL4) are upregulated in this DAD model up to three orders of magnitude compared to the background level. Here we showed that a nonpeptide compound TAK-779, antagonist of CCR5/CXCR3, readily prevents DAD of the lung with a single injection of 2.5 mg/kg. Histological analysis revealed reduced peribronchial and perivascular mononuclear infiltration in the lung, and mononuclear infiltration of the wall and lumen of the alveoli in the TAK-779-treated animals. Administration of the TAK-779 decreased 3-5-fold level of serum cytokines and chemokines in animals with DAD, including CCR5 ligands MIP-1/, MCP-1 and CCL5. Computed tomography revealed rapid recovery of the density and volume of the affected lung in TAK-779-treated animals. Our pre-clinical data suggest that TAK-779 is more effective than administration of dexamethasone or anti-IL6R therapeutic antibody tocilizumab, which brings novel therapeutic modality to TAK-779 and other CCR5 inhibitors for treatment of virus-induced inflammation syndromes, including COVID19.